2022
DOI: 10.3389/fonc.2022.812663
|View full text |Cite
|
Sign up to set email alerts
|

Identification of CFHR4 associated with poor prognosis of hepatocellular carcinoma

Abstract: BackgroundHepatocellular carcinoma (HCC) is one of the most leading causes of cancer death worldwide. The 5-year survival rate of HCC patients remains low due to the lack of early-stage symptoms. Human complement factor H-related protein 4 (CFHR4) is a critical gene that belongs to the factor H family of plasma glycoproteins, which has not been linked to HCC development. The correlations between CFHR4 and prognosis and tumor-infiltrating lymphocytes in HCC are yet unknown. The present study demonstrated the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 62 publications
1
4
0
Order By: Relevance
“…High expression of TRIM47 is associated with poorer overall survival in HCC patients [17]. High G6PD and LPCAT levels suggested a poor prognosis for HCC patients [25][26][27], while CFHR4 was the opposite [28]. This is consistent with our results.…”
Section: Discussionsupporting
confidence: 92%
“…High expression of TRIM47 is associated with poorer overall survival in HCC patients [17]. High G6PD and LPCAT levels suggested a poor prognosis for HCC patients [25][26][27], while CFHR4 was the opposite [28]. This is consistent with our results.…”
Section: Discussionsupporting
confidence: 92%
“…This analysis highlights their potential role in HCC progression and patient prognostic outcomes. Research by Ding Q et al pointed out that CFHR4 is signi cantly low-expressed in HCC, which can lead to poor patient prognosis, and its level of expression and the extent of immune cell in ltration are also correlated (32). The study by Yu H et al further showed the substantial predictive usefulness of CFHR4 in HCC by demonstrating how the expression of this gene and several clinicopathological factors are strongly correlated with immune cell in ltration (33).…”
Section: Discussionmentioning
confidence: 99%
“…There is an urgent need to find new targets for the diagnosis and treatment of liver cancer in the direction of a breakthrough in the current treatment limitations. Some previous studies used TCGA and GEO databases to screen oncogenes and identify prognostic or immune-related genes ( Chen et al, 2020 ; Gao et al, 2021 ; Yan et al, 2021 ; Shen et al, 2022a ; Shen et al, 2022b ; Ding et al, 2022 ; Gao et al, 2022 ; Long et al, 2022 ; Yang et al, 2022 ). However, in this study, four GSE datasets, GSE36376, GSE102079, GSE54236, and GSE45267, were summarized for analysis, hoping to find the mechanism of cancer-promoting and tumor-suppressor factors in liver cancer from the perspective of improving the accuracy of the research results.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, public data and bioinformatic analysis methods have provided us with invaluable resources to find HCC-related oncogenes and tumor-suppressor genes. Some studies searched cancer-related target genes through public databases, whether prognostic oncogene identification ( Gao et al, 2021 ; Yan et al, 2021 ; Shen et al, 2022a ; Gao et al, 2022 ), single-gene research studies ( Ding et al, 2022 ; Yang et al, 2022 ), or immune-related oncogenes ( Chen et al, 2020 ; Shen et al, 2022b ; Long et al, 2022 ), all of which provided a strong basis for targeted therapy and precise treatment of liver cancer. However, many studies only consider the differential expression of oncogenes in tumors, ignoring the important role and potential association of tumor-suppressor genes.…”
Section: Introductionmentioning
confidence: 99%